Inovasi Kewirausahaan Teknologi Berbasis Augmented Reality: Studi Proses Pengembangan Teknologi AR pada Produk Dollipop Bouquet - Salsabila, Nasywa Shafa; Hanifah, Nurrizkyta Aulia; Rachman, Muhammad Aqil Musthafa Ar Rachman; Kuntari, Wien (Journal of Economics, Bussiness and Management Issues, 2024)
Indonesia's creative economy sector has shown significant growth, driven by increasing consumer demand for artistic and personalized products. However, many products in the gift and craft market remain conventional, lacking interactive digital features that appeal to younger consumers. This study addresses this gap by integrating Augmented Reality (AR) technology into Dollipop Bouquet, a personalized doll bouquet, using the Multimedia Development Life Cycle (MDLC) methodology. The research involved six stages: Concept, Design, Material Collecting, Assembly, Testing, and Distribution. By leveraging AR, Dollipop Bouquet allows customers to personalize their gifts with interactive features such as video collages and photo-based markers, accessed via an AR application. The findings demonstrate that AR integration enhances product appeal, providing a unique and meaningful gifting experience. Dollipop Bouquet is the first in Indonesia to combine AR with doll bouquets, marking a breakthrough in the creative industry. This study contributes to the development of AR applications in multimedia-based businesses and highlights its potential for broader applications in personalized marketing and digital interaction. Future research should explore more advanced AR features, such as AI-driven personalization or geolocation-based AR, to further enhance user experiences and expand technological applications across industries.